Ischemic Priapism Progressing to Penile Gangrene in a Patient with COVID-19 Infection: A Case Report with Literature Review - Saad M. Alsaedi; Rakan M. Alsarwani; Ahmed I. Ali; Saleem A. Aladhrai (Case Reports in Medicine)
Priapism is considered a rare disorder and even more rare when it occurs as a complication of COVID-19. To the best of our knowledge, only eight studies have reported priapism as a complication of COVID-19. Here, we report the case of a 66-year-old male with COVID-19 who presented with neglected priapism for three days. On local examination, penile erection was apparent in association with blackened areas on the glans penis extending to the midpenile shaft denoting penile gangrene. A clear line of demarcation was noticed at the midpenile shaft. Penile duplex was performed, showing no blood flow in both cavernosal arteries. Penile aspiration was performed, and the cavernosal blood sample showed evidence of ischemic priapism. Given the presence of penile gangrene extending to the midshaft of the penis and the poor general condition of the patient, the decision was made to perform partial penectomy and suprapubic tube placement. We recommend the establishment of a guideline for the diagnosis and prevention of thrombotic diseases in patients with COVID-19 infection as there is increasing evidence of COVID-19-related thrombotic manifestations.